Greenhouse gas emissions from constructed wetlands are mitigated by biochar substrates and distinctly affected by tidal flow and intermittent aeration modes. (15th February 2021) - Ji, Bohua; Chen, Jinquan; Li, Wei; Mei, Jian; Yang, Ying; Chang, Junjun
Abstract: Biochar substrates and tidal flow (TF) and intermittent aeration (IA) operation modes have recently been applied to improve the treatment performance of constructed wetlands (CWs), but their roles in regulating greenhouse gas (GHG) emissions from CWs are still unclear. In this preliminary study, CO2, CH4 and N2 O fluxes and associated microbial characteristics in four groups of subsurface-flow CWs, i.e., ceramsite CWs (C-CWs), biochar-amended CWs (B-CWs), intermittently aerated B-CWs (AB-CWs) and tide-flow B-CWs (TB-CWs), were comparatively investigated. The results showed that biochar amendment significantly mitigated CH4 and N2 O fluxes from the CWs by supporting higher abundances of mcr A and nos Z genes and higher ratios of pmo A/ mcr A and nos Z/( nir K +  nir S), thus reducing global warming potential (GWP, a decrease of 55.8%), in addition to promoting total nitrogen (TN) removal by 41.3%, mainly by increasing the abundances and activities of nitrifiers and denitrifiers. The TF mode efficiently improved nitrogen removal, but it greatly increased GHG fluxes since large amounts of GHGs escaped from the empty CW matrix after water draining. IA abated GHG emissions from the CWs, mainly after aeration. TF and IA decreased the abundances of functional bacteria and archaea related to C and N transformation, except nitrifiers, and shaped the microbial community structures. The application of a biochar substrate and IA mode can facilitate the design and operation of CWs in a more ecologically sustainable way. Graphical abstract: Image 1 Highlights: Biochar substrates and tidal flow and intermittent aeration effectively enhanced N removal in CWs. Biochar mitigates GHG emissions by supporting higher ratios of pmo A/ mcr A and nos Z/( nir K +  nir S) in CWs. Intermittent aeration reduced GHG emissions from CWs, mainly after aeration. GHG emissions from tidal flow CWs largely increased after water draining. Bacterial and archaeal communities in the CWs were comparatively characterized.